Prognostic stratification in MDS/MPN syndromes other than CMML: an Italian multicenter real-world study - Luca Guarnera; Giuseppe Gaetano Loscocco; Massimo Breccia; Mara Memoli; Bruno Fattizzo; Marta Riva; Ambra Di Veroli; Michelina Santopietro; Giovanni Iaquinta; Annalisa Biagi; Sabrina Leonetti Crescenzi; Caterina Tatarelli; et al. (Clinical and Experimental Medicine, 2026)
Abstract MDS/MPN syndromes comprise a heterogeneous group of myeloid neoplasms. While CMML has been extensively characterized, data on other MDS/MPN entities remain limited, particularly in real-world settings. We conducted a nationwide, multicenter retrospective study including adult patients with MDS/MPN syndromes other than CMML from 17 Italian centers. Patients were classified as MDS/MPN with SF3B1 mutation and thrombocytosis ( SF3B1 -T), atypical chronic myeloid leukemia/chronic neutrophilic leukemia (aCML/CNL), or MDS/MPN not otherwise specified (NOS). A total of 101 patients were included (median age 71 years). MDS/MPN SF3B1 -T showed a significant survival advantage compared with MDS/MPN NOS and aCML/CNL (OS p = 0.0058, LFS p = 0.012). aCML/CNL displayed the worst outcomes and most genetic complexity. Across the overall cohort, IPSS-M demonstrated the highest discriminative ability and calibration accuracy for both OS and LFS, outperforming CMML-directed models, including BLAST-clinical and BLAST-molecular whereas disease-specific scores provided optimal stratification within individual entities but failed to adequately predict outcomes in MDS/MPN NOS. In this real-world analysis, IPSS-M emerged as the most robust prognostic framework across MDS/MPN entities other than CMML. The inability of current tools to reliably stratify patients with MDS/MPN NOS underscores the biological heterogeneity of this category and highlights the urgent need for integrated clinical and genomic prognostic models.